Carbon nanomaterials derived from Malaysia’s highway road asphalt waste as electrode for supercapacitor - Mohd Abid, Mohd Asyadi Azam; Raja Seman, Raja Noor Amalina; Zulkifli, Mohd Fadzil; Mohamed, Mohd Ambri; Ani, Mohd Hanafi (University of Mohammed Premier, Oujda Morocco, 2018)
Developing cost-effective and environmental friendly electrode material for supercapacitor is critical for energy storage technologies. The fabrication of asphalt waste carbon (AWC) combined with multi-walled carbon nanotube (MWCNT) supercapacitor electrode was performed by using conventional slurry technique. The AWC/MWCNT composite electrode was compared to that of non-mixed AWC electrode. For non-mixed AWC electrode, the specific gravimetric capacitance (Csp) was 1.93 F g-1 at 1 mV s-1 scan rate and the Csp obtained for AWC/MWCNT electrode was 62.94 F g-1. From charge-discharge analysis, the AWC/MWCNT electrode showed nearly symmetrical triangular shapes at different current densities (0.5 to 15 A g-1). It was also clear that the Csp remains about 80% of the initial capacitance after 800 cycles at 15 A g-1 current density, indicating that AWC/MWCNT electrode possessed good ion accessibility and cycling stability.